Destratification in the Progenitor Interior of the Mg-rich Supernova Remnant N49B - Toshiki Sato; Kai Matsunaga; Ryo Sawada; Koh Takahashi; Yudai Suwa; John P. Hughes; Hiroyuki Uchida; Takuto Narita; Hideyuki Umeda (The Astrophysical Journal)
Simulations of presupernova evolution suggest that intense O-shell burning can be so active that, in extreme cases, it can merge with the outer C-burning shell, changing the initial conditions for the supernova explosion. However, such violent activity in the interior of stars has been difficult to confirm from observations of stars. Here we propose that the elemental composition of O-rich ejecta in supernova remnants (SNRs) can be a tool to test for this kind of intense shell burning activity in the final stages of progenitor evolution. As an example, we discuss the origin of “Mg-rich” ejecta in the SNR N49B. A high Mg/Ne mass ratio ≳ 1 suggests that the Ne- or O-burning shell has broken into or merged with the outer shell before the collapse. Such Mg-rich (or Ne-poor) ejecta has been identified in some other SNRs, supporting the idea that some destratification process, such as a shell merger, does indeed occur in the interiors of some massive stars, although they may not be the majority. Our results suggest that X-ray observations of O-rich ejecta in core-collapse SNRs will be a unique tool to probe the shell burning activity in the stellar interior during the final weeks to days of a massive star’s evolution.